Application of Traditional Chinese Medicine collapse stains combined with hand rehabilitation exercises in a patient with grade 1 phlebitis and related nursing measures (中药塌渍联合手部康复操治疗Ⅱ级静脉炎1例的护理) - JIA Tieying (贾铁英); YANG Yu (杨宇); FAN Yan (范艳); LI Chenchen (李陈晨); HU Shirong (胡世荣) (Association of Integrative Nursing, 2021)
This paper summarized the nursing experience of a patient with grade 1 phlebitis treated by Traditional Chinese Medicine collapse stains combined with hand rehabilitation exercise. Nursing evaluation was carried out before intervention, and Traditional Chinese Medicine collapse stains combined with hand rehabilitation exercises were performed according to the evaluation outcomes. In the meantime, health education was conducted to improve the disease awareness and treatment compliance of the patient. (本文总结中药塌渍联合手部康复操治疗1例Ⅱ级静脉炎患者的护理经验。干预前需要进行科学评估, 根据评估结果开展中药塌渍联合手部康复操干预, 同时做好健康宣教, 提升患者认知, 提高治疗依从性。)